Effects of Palm-Tocotrienol Rich Fraction (TRF) on MRP2 Protein Expression in Bilirubin Transport in adult rats - Ismawi, Hidayatul Radziah; Mohd Saad, Qodriyah; Ahmad Yusof, Asmadi; Othman, Faizah; Yusuf, Kamisah (2010)
Unconjugated hyperbilirubinaemia in adults, although are usually mild, sometimes require treatment to improve quality of life and prevent complications. MRP2 as an efflux protein for bilirubin transport is crucial in its elimination. Vitamin E has previously been shown to reduce hyperbilirubinaemia. Palm oil is rich in tocotrienols with potent antioxidant properties. This study explores the effect of pre-treatment with palm-tocotrienol rich fraction (TRF) on phenylhydrazine (PHZ) induced hyperbilirubinaemia in adult rats on plasma total bilirubin levels and MRP2 protein expression. Fourty-eight adult male wistar rats (200-250g) were divided into 3 groups, TRF (i.p. 100mg/kg/day for 14 days), phenobarbital (i.p. 80mg/kg/day for 5 days) and control (i.p. palm oil without Vitamin E for 14 days)On Day 15, the groups were further subdivided into 2 groups where 8 rats from each treatment group were either given intraperitoneal PHZ 100mg/kg to induce hyperbilirubinaemia or normal saline. Plasma total bilirubin (TB) was measured after 24 hours. Microsomes were prepared from liver samples and Western Blot analysis of MRP2 was performed. TB was significantly higher in the control PHZ induced group (0.19mg/dL +- 0.026) compared to its non-induced group (0.06mg/dL +- 0.008. TRF failed to reduce the increase in TB in both PHZ induced and non-induced groups. Relative protein expression of MRP2 was significantly higher for TRF+PHZ (1.42 +- 0.005) and phenobarbital+PHZ groups 1.24+- 0.020) compared to the control PHZ group with a significant difference between these groups and the TRF non-induced group (1.04 +- 0.016). In conclusion, PHZ induces hyperbilirubinaemia in the rat model but does not increase MRP2 expression. TRF failed to reduce the increase in TB but it elevated the protein expression of MRP2 significantly compared to PHZ group. Although the protective effects of TRF is not refelected in the decrease of plasma TB, its role in the treatment of hyperbilirubinaemia should be further explored.